Sportskammerater - et tema i forholdet mellem lokale idrætsforeninger og kommunale myndigheder - Mortensen, Morten (Forum for Idræt, 2002)
Idrætspolitik og idræt som socialt samlingspunkt. Sporting comrades – a theme in the relationship between local sports associations and the county authorities Up until the Leisure Bill of 1968, relations between local sporting associations and local authorities were characterised by a gradual onward progress, in which local sports associations with greater or lesser degrees of success won the local power struggle to give children and young people a good leisure activity. Those rights and agreements with the county on economic support which most sports associations today almost take for granted were achieved because the self-knowledge possessed by sports associations was shared in a whole series of areas by surrounding society and to a large degree also by politicians. Central to this self-knowledge was the perception that comradeship in sports associations symbolised a social fellowship which was held in place by emotional values. The question is whether comradeship is not in many ways at the heart of the way in which sports associations have locally extended and underpinned their influence in relation to local politicians and business. To take part in the comradely conventions of sport was then tantamount to being member of a lodge with all the political and economic network that it involved.